Evolution of Ischemic Cerebrovascular Disease in patients with Metabolic Syndrome - yanneris parada barroso; Yaima Hechavarría Córdoba; Yoany Mesa Barrera; Tania Elena Hernández Rodríguez (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Cerebrovascular ischemia represents the highest incidence and prevalence among cerebrovascular diseases. It is frequently associated with Metabolic Syndrome because many risk factors for cerebrovascular ischemia correspond to this entity. Objective: To determine the relationship between the evolution of the patient with Acute Ischemic Cerebrovascular Disease (AICVD) and the presence of Metabolic Syndrome (MS). Material and Methods: An analytical prospective study was conducted with a sample of 100 patients, which were divided into two groups: group A, that was composed of patients with Metabolic Syndrome (MS) according to NCEP/ATPIII criteria (The Adult  Treatment Panel III of the National Cholesterol Education), and group B that was composed of patients without Metabolic Syndrome. The National Institutes of Health Stroke Scale (NIHSS) was applied in both groups to evaluate the severity and evolution of cerebrovascular disease. Results: The Male sex (60%), and white people (52%) prevailed in the group with MS, and the mean age was 61,2 years. The main personal pathological antecedents were Arterial hypertension, cardiopathies, and smoking habit. The severity of cerebrovascular disease on admission was worse in group A (mean: 13,2). These patients presented a greater number of neurological complications such as: intracranial hypertension and convulsions (12%); they also presented non-neurological complications such as: bronchopneumonia (40%), and ulcers resulting from time spent on supine position (28%) with a higher risk (OR: 6,2).  After discharge from hospital, 36% of patients with MS got worse, according to Scale NIHSS. Conclusions: The metabolic syndrome is a risk factor that increases the risk of complications in Ischemic Cerebrovascular Disease and worsens its evolution and prognosis. Keywords: cerebral ischemia, metabolic syndrome (MS), complications, evolution, dyslipidemia, risk factors.